ESTIMASI DAMPAK EKONOMI KONVERSI HUTAN MANGROVE MENJADI PERTAMBAKAN DI DELTA MAHAKAM KABUPATEN KUTAI KARTANEGARA (ESTIMATING OF ECONOMIC IMPACT OF CONVERSION MANGROVE FOREST INTO SHRIMP POND IN MAHAKAM DELTA DISTRICT OF KUTAI KARTANEGARA - Yunianto Setiawan; Dietrich G. Bengen; Cecep Kusmana; Setyo Pertiwi (Environmental Research Center (PPLH) of Udayana University, 2014)
Degradation of mangrove forest in Mahakam Delta were caused by conversion into ponds.These conditions resulted in a decrease in the benefits of the mangrove ecosystem, bothdirectly and indirectly. To restore the environmental conditions, the government rehabilitatingponds by applying sylvofishery pond system. This study aims to estimate the value ofexternalities mangrove areas converted to ponds in the Mahakam Delta and counting analysisfurther aquaculture with traditional extensive system as well as sylvofishery system. From theresult of study, it can be concluded that value of the lost benefits that reach Rp. 137,484,760,721, - / year of mangrove forests that have been converted to ponds for 75,311 ha. NVPvalue was negative and BCR less than 1 for traditional extensive pond system which meansthat the use of ponds with extensive traditional system will suffer a loss and this business wasnot feasible at this time as well as the positive value of BCR and NVP more than1 for thesylvofishery pond system means that utilization of ponds with sylvofishery system will beprofitable and feasible at this time